Babel' in Context - Sicher, Efraim (Academic Studies Press, 2012)
Intro – Contents – Note on References and Translations – Acknowledgments – Introduction – 1 Isaak Babelʹ: A Brief Life – 2 Reference and Interference – 3 Babelʹ, Bialik, and Others – 4 Midrash and History: A Key to the Babelesque Imagination – 5 A Russian Maupassant – 6 Babel''s Civil War – 7 A Voyeur on a Collective Farm – Bibliography of Works by Babelʹ and Recommended Reading – Notes – Index.
Description based on publisher supplied metadata and other sources
Keywords: Babel'; I. – (Isaak); – 1894-1940; Authors; Russian; Babelʹ; I; (Isaak); 1894-1940; Electronic books